Need Analysis for Air Conditioners in Public Sector of Surabaya City Government - Dwiarti Larasputri (Jurnal Teknik ITS, 2016)
In typical buildings, air conditioners have the biggest percentage in energy consumption among all sectors. It makes a good management for air conditioners is needed and important in order to use the energy efficiently. Having a very hot and humid weather, it gives impact that most of buildings in Surabaya installed air conditioners, including Surabaya City Government office buildings. However, there is no regulation nor guidance how to manage air conditioners in Surabaya City Government, while Surabaya itself has a goal to become a green-eco city. Then, the existing condition of air conditioners usage in Surabaya Government units (SKPDs) is evaluated. The evaluation resulted that most of air conditioners were over capacity and not all of them were efficient in energy consumption. Therefore, a need analysis is required to help Surabaya City Government managing its air conditioners better. By applying two different concepts, one is based on the architectural view and another one is based on green building criteria, the existing condition is analyzed and two procedures of need analysis are produced. The procedures can be implemented for two different conditions of office building rooms in Surabaya City Government.